THE IMPORTANCE OF INNOVATION IN THE HIGHER EDUCATION SYSTEM AND ITS IMPORTANCE IN ECONOMIC DEVELOPMENT (Universal International Scientific Journal, 2026)
This article examines the role of innovation in higher education and its significance for economic development. Particular attention is paid to the integration of education, science, and industry as a key factor in innovative development. The paper analyzes the improvement of research activities, the effective use of intellectual resources, and the training of highly qualified personnel. It also examines the priority areas of an innovative development strategy and the role of higher education institutions in advancing scientific and innovative activity. It concludes that strengthening the interaction between education, science, and industry is essential for sustainable economic growth.
Keywords: innovation, higher education system, innovative development, science-education-production integration, scientific and research activities, knowledge economy, highly qualified personnel, innovative infrastructure, economic growth.